Overview: Getting Involved in Research as a Busy Practicing Surgeon - Kennedy, Gregory D. (Clinics in Colon and Rectal Surgery, 2014)
To succeed in academic surgery in the current era, it is important that a surgeon brings a unique attribute that enhances the mission of the institution beyond the scope of surgical mastery and relative value units (RVUs). Given the increasing pressure on a surgeon to produce RVUs, how can a prospective surgical scientist successfully develop and maintain a research program? The establishment of a successful research program requires planning that begins in surgical residency and careful decision making along the way with clear focus of goals. This article will provide insight into the steps to consider along the way as you work to establish your successful research program.
Keywords: academic colorectal surgery; research